Implementation of Qual2Kw and MCDA in Formulating Sustainable River Water Quality Standard Compliance Program Policies: A Case Study of the Cileungsi River in Bogor Regency - Muhamad Komarudin; Anas M Fauzi; Yanuar J Purwanto; Hartrisari Hardjomidjojo; Budi Kurniawan (Green Publisher Indonesia, 2026)
This study aims to develop an integrative approach between water quality modeling using QUAL2Kw software and the Multi-Criteria Decision Analysis (MCDA) method with PROMETHEE software to support the formulation of policies for sustainable river water quality standards. The study was conducted on the Cileungsi River, West Java, with key parameters of BOD, COD, and TSS. Modeling was carried out in four tiered scenarios representing existing conditions and quality standards targets of classes IV, III, and II, thus providing a basis for designing technical interventions such as reducing point source and non-point source pollutant loads, increasing upstream discharge, and improving upstream water quality. Based on the results of iterations and model observations, six policy criteria (K1–K6) and twelve program alternatives (P1–P12) were obtained to achieve river water quality standards. PROMETHEE analysis was used to determine program priorities based on stakeholder preference weights. The results of the study show that the integration of QUAL2Kw–PROMETHEE is able to provide a more measurable scientific and policy basis, with the main priorities being the development and improvement of IPAL performance, control of non-point sources, and an increase in river base discharge. This approach has the potential to be applied as an evidence-based policy decision-making model in river water quality management in Indonesia.